Peran Stakeholder Suatu Instansi Pendidikan dalam Mencapai Keefektifan Pembelajaran - Muhammad Habib Zainul Huda; Sugiyo Sugiyo (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
Learning in educational institutions today can be said to lack effectiveness. This is certainly there are things that hinder, both from within the educational institution or from outside the educational institution. This research aims to describe how effective learning actually is, and what are the roles of stakeholders in achieving effective learning. This research includes qualitative research with a descriptive analysis approach. The theory that the author uses is the theory of Phenomenology, which this theory tries to look more at the phenomena that occur in an educational institution. The conclusions of this study are: (1). Effective learning is learning that prioritizes Akhlaq, Local Value-Based Learning, and Humanist Learning. (2). Among the roles of stakeholders in realizing effective learning are: Being a good Leadershep Good Leaders, Planning Innovative Strategies, and Implementing Programs to the Maximum.